A Funeral Duet for Humboldt? The Rise and Decay of Humboldtian Thought in Contemporary Higher Education in Germany - Yuan-Chuan Chang (National Taipei University of Education, 2017)
Between the middle of the 19th century and the Second World War German universities developed into top-notch centers of academia. Wilhelm von Humboldt is widely recognized as a pivotal figure in this development and his ideas have been widely influential throughout the world. Nonetheless, some have called into question the "myth of Humboldt." In this paper, I investigate the relationship between Humboldtian thought and higher education in Germany on both the practical level and the level of university idea. On the practical level, as a result of the shift to mass education in the 1960s, the Humboldtian thought began to be eclipsed by a new emphasis on competition, efficiency, and achievement. On the level of university idea, there has long been a tense relationship between Humboldtian thought and modern science; further, the industrial revolution lent much impetus to the development of science, which has been further bolstered by institutions characterized by competition and division of authority. Moreover, institutions characterized by role hybridization tend to have an integrating influence on theoretical and experiential research in various fields, which tends to spur scientific innovation. In such a situation, Humboldt's ideas can be likened to a switchman for steering stagnant German universities back onto the track of research imbued with the spirit of exploration, an approach which has given rise to the so-called "Berlin University model."